Power forward - Khan, Hena; Comport, Sally Wern (New York : Salaam Reads, 2018)
Fourth-grader Zayd yearns to play basketball on the Gold Team, but when he skips orchestra rehearsal to practice, his parents forbid anything basketball-related, and tryouts are coming soon.
School Library Journal, May 2018
Booklist, April 2018
Kirkus Review, March 2018
5.4
3-6
600L
Keywords: Basketball -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Families -- Juvenile fiction; Honesty -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Basketball -- Fiction; Pakistani Americans -- Fiction; Family life -- Fiction; Honesty -- Fiction; Middle schools -- Fiction; Schools -- Fiction